4 pedicle screw mono-segment versus 6 pedicle screw short-segment fixation in the treatment of thoracolumbar endplate fractures: finite element analysis and clinical follow-up - He, Kai; Liu, Shengxiang; Li, Feng; Yang, Xuejun; Xing, Wenhua (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo compare the finite element analysis and clinical follow-up of posterior 4 pedicle screw mono-segment and 6 pedicle screw short-segment pedicle screw fixation techniques in the treatment of thoracolumbar endplate fractures of the spine.MethodsThe finite element method was used to analyze the treatment of thoracolumbar upper endplate or lower endplate burst fractures with posterior 4 pedicle screw mono-segment and 6 pedicle screw short-segment pedicle screw fixation techniques (UM: upper endplate fracture + mono-segment pedicle screw fixation [UEPF + MPSF], US: upper endplate fracture + short-segment pedicle screw fixation [UEPF + SPSF], LM: lower endplate fracture + mono-segment pedicle screw fixation [LEPF + MPSF], LS: lower endplate fracture + short-segment pedicle screw fixation [LEPF + SPSF]). 2. A retrospective analysis was conducted on 77 patients with mild to moderate thoracolumbar spine fractures of type A3.1 admitted from October 2019 to October 2024. Among them, 38 patients underwent posterior 4 pedicle screw mono-segment, and 39 patients underwent posterior 6 pedicle screw short-segment fixation. The perioperative performance, clinical functional performance, and imaging performance were compared between the two groups.ResultsFinite element analysis and prediction based on specific models: In fractures of the same type, the range of motion (ROM) in all directions of 4 pedicle screw mono-segment fixation showed a trend of higher values compared with 6 pedicle screw short-segment fixation, while the von Mises stress of adjacent intervertebral discs and adjacent facet joints showed a trend of lower values compared with 6-screw short-segment fixation. The 6 pedicle screw short-segment fixation model predicted that the maximum displacement of the fixed segment, the mobility of the fixed segment, and the mobility of the injured vertebra were smaller than those of 4 pedicle screw mono-segment fixation. The peak von Mises stress values of screws in the US, UM, LS, and LM groups were 386.61 Mpa, 397.60 Mpa, 302.63 Mpa, and 305.59 Mpa, respectively; the peak von Mises stress values of rods in these groups were 416.22 Mpa, 446.18 Mpa, 329.03 Mpa, and 347.47 Mpa, respectively. The stress of the injured vertebra in 6 pedicle screw short-segment fixation showed a trend of lower values compared with 4 pedicle screw mono-segment fixation. With the same fixation method, the predicted ROM of the lower endplate fracture model was larger than that of the upper endplate fracture model. The upper endplate fracture model predicted that the peak von Mises stress of adjacent intervertebral discs and facet joints appeared at the proximal end, and the stress of proximal screws was high; in contrast, the lower endplate fracture model predicted that the peak von Mises stress of adjacent intervertebral discs and facet joints appeared at the distal end, and the stress of distal screws was high. The maximum displacement of the fixed segment, the mobility of the fixed segment, and the mobility of the injured vertebra in lower endplate fractures showed a trend of lower values compared with upper endplate fractures. The stress of the screw-rod system and the injured vertebra in lower endplate fractures showed a trend of lower values compared with upper endplate fractures. 2. Clinical outcomes mainly for upper endplate fractures: ① Perioperative performance: The operation time, blood loss volume, drainage volume, time to weight-bearing time, and length of hospital stay in the 4 pedicle screw mono-segment group were all significantly lower than those in the 6 pedicle screw short-segment fixation group (P < 0.05). ② Clinical functional performance: Immediately after surgery, the Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) in the 4 pedicle screw mono-segment group were significantly lower than those in the 6 pedicle screw group (P < 0.05); there were no significant differences in VAS, ODI, or Japanese Orthopaedic Association (JOA) between the two groups at other time points (P > 0.05). All three scores showed significant improvement over time (P < 0.05). ③ Imaging performance: There were no significant differences in the anterior vertebral height (AVBH), posterior vertebral heigh (PVBH), or Cobb angle between the two groups before surgery, immediately after surgery, or at long-term follow-up (P > 0.05). Within each group, the AVBH, PVBH, and Cobb angle immediately after surgery and at long-term follow-up were significantly better than those before surgery (P < 0.05); compared with immediately after surgery, the corrected values of these indicators were lost at long-term follow-up (P < 0.05).ConclusionFinite element analysis and prediction based on specific models: Both 4 pedicle screw mono-segment fixation and 6 pedicle screw short-segment fixation are effective methods for treating thoracolumbar burst fractures of the spine. The 4 pedicle screw mono-segment fixation may be suitable for patients with normal bone mineral density and mild-to-moderate fractures, with advantages of preserving spinal mobility and reducing the risk of adjacent segment degeneration. The 6 pedicle screw short-segment fixation has a wider application range, and its advantages lie in better stability and stress dispersion. For upper endplate fractures, the adjacent segment at the proximal end is the stress concentration area, and the proximal screws bear the maximum stress; in contrast, for lower endplate fractures, the adjacent segment at the distal end is the stress concentration area, and the distal screws bear the maximum stress. The stability gap between 4 pedicle screw mono-segment fixation and 6 pedicle screw short-segment fixation is smaller in lower endplate fractures than in upper endplate fractures. Compared with upper endplate fractures, lower endplate fractures show better overall performance and may have a better prognosis. However, different finite element models may be required in the future to reduce the impact of individual differences. 2. Clinical outcomes mainly for upper endplate fractures: For mild-to-moderate fractures, the 4 pedicle screw mono-segment fixation achieves the same reduction effect as the 6 pedicle screw short-segment fixation both immediately after surgery and during long-term internal fixation removal. Moreover, it has advantages such as shorter operation time, smaller incision, less blood loss, earlier weight-bearing time, shorter hospital stay, less early postoperative pain, and faster functional recovery. However, more cases of lower endplate fractures may need to be collected in the future for further verification.